Animal Models of Nicotine Exposure: Relevance to Second-Hand Smoking, Electronic Cigarette Use, and Compulsive Smoking - Cohen, Ami; George, Olivier (Frontiers in Psychiatry, 2013)
Much evidence indicates that individuals use tobacco primarily to experience the psychopharmacological properties of nicotine and that a large proportion of smokers eventually become dependent on nicotine. In humans, nicotine acutely produces positive reinforcing effects, including mild euphoria, whereas a nicotine abstinence syndrome with both somatic and affective components is observed after chronic nicotine exposure. Animal models of nicotine self-administration and chronic exposure to nicotine have been critical in unveiling the neurobiological substrates that mediate the acute reinforcing effects of nicotine and emergence of a withdrawal syndrome during abstinence. However, important aspects of the transition from nicotine abuse to nicotine dependence, such as the emergence of increased motivation and compulsive nicotine intake following repeated exposure to the drug, have only recently begun to be modeled in animals. Thus, the neurobiological mechanisms that are involved in these important aspects of nicotine addiction remain largely unknown. In this review, we describe the different animal models available to date and discuss recent advances in animal models of nicotine exposure and nicotine dependence. This review demonstrates that novel animal models of nicotine vapor exposure and escalation of nicotine intake provide a unique opportunity to investigate the neurobiological effects of second-hand nicotine exposure, electronic cigarette use and the mechanisms that underlie the transition from nicotine use to compulsive nicotine intake.